Preferensi Materi Penyuluhan Pertanian Organik di Wilayah Pesisir Bone Bolango, Indonesia - Karlena Arsyad; Zulham Sirajuddin; Nur Silfiah Amin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Organic farming is crucial for the sustainability of coastal ecosystems, yet its adoption in Bone Bolango Regency remains low due to suboptimal extension strategies. This study employs a mixed methods approach aimed at: (1) identifying priority materials for farmers in Bone Bolango; (2) analyzing extension need gaps; and (3) formulating participatory extension strategies to accelerate the adoption of organic farming. Data were collected through a survey of 366 farmers and in-depth interviews with 20 key informants. The analysis employed the Rank Discrepancy Score (RDS) to measure gap needs and thematic analysis for qualitative data. Results indicate that farmers prioritize technical materials, specifically pest and disease control (RDS = 4.21) and organic fertilization (RDS = 3.87), while institutional aspects are considered less urgent. The Wilcoxon test confirmed a significant gap (p < 0.001) between the importance of materials and farmers’ current understanding. This study recommends reorienting extension strategies to be more participatory and focused on practical technical solutions to enhance organic farming adoption in coastal areas.